Neuropsychological manifestations in rheumatic patients with chronic pain - Tomašević-Todorović Snežana; Nožica-Radulović Tatjana; Popović Tamara; Milićević Saša; Savić Damjan; Spasojević Tijana; Bošković Ksenija (Srpski Arhiv za Celokupno Lekarstvo, 2023)
Introduction/Objective. Patients with rheumatoid arthritis (RA), osteoarthritis and fibromyalgia, alongside chronic pain, often suffer from functional disabilities, as well as cognitive dysfunction. The objective of this study is to compare the intensity of pain, symptoms of depression, anxiety, and memory ability among rheumatic patients with chronic pain and to compare rheumatic patients to a control group of healthy participants. Methods. The cross-sectional study, which included 110 (82 female; 28 male) patients with chronic pain, was done at the Special Hospital for Rheumatic Diseases, Novi Sad. Depression was determined by Beck’s Depression Inventory, anxiety was diagnosed by Spielberger’s anxiety test, and memory was assessed by the Wechsler Memory Scale. Results. Mean pain intensity in patients with fibromyalgia were statistically significantly higher compared to patients with osteoarthritis and RA (p < 0.05). A statistically significant difference in the psychological status of patients (p < 0.001) and patient memory (p < 0.05) with chronic pain was established, compared to patients in the control group. There was no statistically significant difference in the psychological status of patients, patient memory level, and pain intensity in patients with positive fibromyalgia test results in comparison to rheumatic patients not meeting the criteria for fibromyalgia. Patients with osteoarthritis had a statistically significantly lower memory coefficient in comparison to patients with RA and fibromyalgia. Conclusion. In RA, osteoarthritis, and fibromyalgia patients, clinical factors such as pain, depression, and anxiety play an active role in cognitive impairment and should be considered when planning treatment.